PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK (Studi Kasus SMK Al-Wathoniyah Pusat Putri) - Faris Hissi; Nahuda; Kunaenih; Fauzan Hamdi; Yayah, Husheini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning motivation remains a significant challenge in the learning process. One of the factors suspected to influence this condition is teacher competence in implementing learning. Teacher competence, which includes pedagogical, professional, personality, and social aspects, plays a role in creating a conducive learning environment, enhancing teacher-student interaction, and fostering learning interest. This study aims to determine the effect of teacher competence on student learning motivation at SMK Al-Wathoniyah Pusat Putri. The research method used is quantitative with a correlational approach. The population consisted of all 205 students at SMK Al-Wathoniyah Pusat Putri, with a sample of 68 students determined using the Slovin formula. Data were collected using a Likert-scale questionnaire. Data analysis employed simple linear regression with SPSS version 26. The results show a positive and significant effect of teacher competence on student learning motivation, evidenced by a correlation coefficient (R) of 0.622 indicating a moderate relationship. The coefficient of determination (R Square) of 0.387 indicates that 38.7% of the variation in student learning motivation is explained by teacher competence, while the remaining 61.3% is influenced by other factors. Hypothesis testing shows a significance value < 0.05, thus H₀ is rejected and Hₐ is accepted. Keywords: Teacher Competence, Learning Motivation